Research on the Effect of Human Resource Management on Innovation at Vietnam Electricity Corporation - Anh, Nguyen Ngoc; Huong, Dinh Thi (VNU JOURNAL OF ECONOMICS AND BUSINESS; Vol 2 No 2, 2022)
This research aims to analyse the effect of human resource management on innovation and creativity at Vietnam Electricity Corporation. Data from 765 questionnaires from Vietnam Electricity Corporation were processed through SPSS software and AMOS 21, then descriptive statistics, exploratory factor analysis (EFA), confirmatory factor analysis (CFA), SEM analysis and a Bootstrap test were performed. The result shows that the factors of human resource management that affect innovation at EVN include: Recruitment of employees and training and development and performance appraisal. Of these, training and development is the factor that has the strongest impact on innovation and creativity at EVN. At the same time, the research also proposes some policy implications for managers at Vietnam Electricity Corporation to promote the activity of human resource management and innovation to enhance the efficiency of the corporation’s operation.